2015
DOI: 10.1155/2015/760405
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract ofFicus caricaLinn. Leaves Exerts Antiangiogenesis Effects Based on the Rat Air Pouch Model of Inflammation

Abstract: The antiangiogenesis effect of Ficus carica leaves extract in an air pouch model of inflammation was investigated in rat. Inflammation was induced by injection of carrageenan into pouches. After antioxidant capacity and total phenolic content (TPC) investigations, the extract was administered at 5, 25, and 50 mg/pouch, and then the volume of exudates, the cell number, TNFα, PGE2, and VEGF levels were measured. Angiogenesis of granulation tissues was determined by measuring hemoglobin content. Based on the DPPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Leukocyte accumulation and volume of exudate were significantly inhibited by the extract. It also significantly decreased the production of TNFα, PGE2, and VEGF, while angiogenesis was significantly inhibited by all administered doses [110]. [56].The anti-inflammatory effect of petroleum ether, chloroform and ethanol extracts (300 and 600 mg/kg) of the leaves of Ficus carica was studied by carrageenan-induced rat paw edema and cotton pellet granuloma methods.…”
Section: Anti-angiogenic Effectmentioning
confidence: 99%
“…Leukocyte accumulation and volume of exudate were significantly inhibited by the extract. It also significantly decreased the production of TNFα, PGE2, and VEGF, while angiogenesis was significantly inhibited by all administered doses [110]. [56].The anti-inflammatory effect of petroleum ether, chloroform and ethanol extracts (300 and 600 mg/kg) of the leaves of Ficus carica was studied by carrageenan-induced rat paw edema and cotton pellet granuloma methods.…”
Section: Anti-angiogenic Effectmentioning
confidence: 99%
“…A recent in vivo study showed that leukocyte accumulation and the production of TNFα, PGE2, and VEGF were significantly decreased. Angiogenesis was significantly inhibited by all administered doses of fig extract [47]. Interestingly, the angiogenesis and inflammation parameters exerted by the extract were similar to those of diclofenac.…”
Section: Anti-angiogenic Effects Of Natural Herbsmentioning
confidence: 63%
“…Furthermore, it significantly decreased the production of tumor necrosis factor-α, prostaglandin E2, and vascular endothelial growth factor, whereas angiogenesis was significantly inhibited through all administered doses [48].…”
Section: Anti-angiogenic Effectmentioning
confidence: 95%
“…Result revealed that the extract had significant antioxidant activity with total phenolic content of 11.70 mg gallic acid equivalents/100 g dry sample [48]. Furthermore, it significantly decreased the production of tumor necrosis factor-α, prostaglandin E2, and vascular endothelial growth factor, whereas angiogenesis was significantly inhibited through all administered doses [48].…”
Section: Anti-angiogenic Effectmentioning
confidence: 98%